Snowball throwing learning strategy and learning motivation: keys to success in improving science learning outcomes for high class students - Mariam, Siti; Sapriati, Amalia; Suroyo, Suroyo (Universitas Ahmad Dahlan, 2024)
Snowball Throwing is a pedagogical strategy that employs ice balls or